Hidden Hazards Revealed: Mycotoxins and Their Masked Forms in Poultry - Hamada Okasha; Bochen Song; Zhigang Song (Toxins, 2024)
The presence of mycotoxins and their masked forms in chicken feed poses a significant threat to both productivity and health. This review examines the multifaceted impacts of mycotoxins on various aspects of chicken well-being, encompassing feed efficiency, growth, immunity, antioxidants, blood biochemistry, and internal organs. Mycotoxins, toxic substances produced by fungi, can exert detrimental effects even at low levels of contamination. The hidden or masked forms of mycotoxins further complicate the situation, as they are not easily detected by conventional methods but can be converted into their toxic forms during digestion. Consequently, chickens are exposed to mycotoxin-related risks despite apparently low mycotoxin levels. The consequences of mycotoxin exposure in chickens include reduced feed efficiency, compromised growth rates, impaired immune function, altered antioxidant levels, disturbances in blood biochemical parameters, and adverse effects on internal organs. To mitigate these impacts, effective management strategies are essential, such as routine monitoring of feed ingredients and finished feeds, adherence to proper storage practices, and the implementation of feed detoxification methods and mycotoxin binders. Raising awareness of these hidden hazards is crucial for safeguarding chicken productivity and health.